GAMBARAN PERILAKU PENGHUNI TENTANG PERSONAL HYGIENE DAN SANITASI DASAR, KOMPONEN FISIK DAN FASILITAS SANITASI DASAR, SERTA KELUHAN KESEHATAN KULIT PENGHUNI DI ASRAMA PUTRI USU TAHUN 2014 - Hamidah Fadhilah; taufik ashar; indra chahaya (Lingkungan dan Kesehatan Kerja, 2014)
A university student dormitory is a residence where the students can inhibit as long as they are studying in the university. A resident is supposed to have its influences for people health related to their health behavior and availability of basic sanitation facilities. Problem in insufficiency clean water supply can cause skin health complaints at the dormitory. The type of this research was descriptive survey. This research aimed to describe the knowledge, attitude, and actions of inherences about personal hygiene and basic sanitations, physical components and basic sanitation facilities, and skin health complaints of inherences at USU female dormitory. This research used systematic random sampling technique. There were 15 persons at old USU female dormitory and 60 persons at new USU female dormitory which were participated as samples. The result of this study showed that 73,3% of respondents at old USU female dormitory had good knowledge; 93,3% of respondents had good attitude; 93,3% of respondents had good actions about personal hygiene and basic sanitation. There were 73,3% of respondents at new USU female dormitory had good knowledge; 93,3% of respondents had good attitude; 80,0% of respondents had good actions about personal hygiene and basic sanitation. Percentage of respondents whose skin health complaints were 60,0% at old USU female dormitory and 78,3% at new USU female dormitory. All physical components in USU female dormitory had already met the health requirements but the basic sanitation facilities had not. The manager of dormitory was expected to give more concern to serve basic sanitation facilities which meet the health requirements, especially in supplying clean water which wass sufficient in quantity, continuality, and quality. It was expected to the inhabitants to keep personal hygiene and to use basic sanitation facility well to avoid skin diseases and for those who had skin health complaints to have medical treatment. Keywords : Student Dormitory, Personal Hygiene, Basic Sanitation, Skin Health Complaint